(untitled) (Journal of the College of Basic Education, 2023)
Most educational systems have given great attention to teacher preparation, due to the teacher’s significant impact onThe development of the educational system in general, and the social structure and development of children in particular.Many of the educational systems in the advanced industrial countries have many distinguished studies, especiallyFor research and study in the field of teacher preparation in order to reach the best formulas and methods of educational systems.Preparation. In our country, this interest appeared through a series of conferences, seminars and seminars.Discussions, whether at the level of the Ministry of Education and its affiliated institutions, or at the level of universities.As a culmination of this research, what was mentioned in the national conferences of the Arab Socialist Baath Party, includingThe Eighth National Conference of the party is the best evidence of that interest, and the paper of the Ministry of Higher Education wasAnd scientific research is a great achievement on the way to transforming teacher preparation from a level below a bachelor’s degree.to the bachelor’s level, by establishing teachers’ colleges, as it aims to prepare armed teachersin the theoretical and practical aspects and educationally qualified to be a teacher able to perform his civilized role properlyDeveloped modern. Because the importance of the teacher comes in terms of the platform that the society established to achieve its goals.On the one hand, he is the trustworthy custodian of his cultural heritage, and on the other hand, the greatest factor inRenewing and enhancing this heritage.The teacher is considered the cornerstone of the educational process, and he occupies the forefront of the success of the educational process.Learning in school, as it can modify many of the students’ values and attitudes by regulatingThe educational process and its control, the use of educational techniques, the knowledge of students’ needs and their ways of thinking.and teach them (1).